History of Cuppping in Medical Perspective - Tanjung, Qadri Fauzi; Prima, Agus (Journal of Society Medicine, 2022)
Cupping or Al-hijamah is the process of removing harmful blood/toxid-toxins (static) from the body, through the surface of the skin or the process of removing harmful blood/toxid-toxins (static) from the body, through the surface of the skin. The cupping method of treatment has actually been mentioned in the historical records of various great civilisations of the world, including Egypt, China, India, Europe and America. So that various cupping terms are known in the world in various languages including kop, cucurbit, cupping, fire-bottle, blood-letting, pa hou kuan (Mandarin). Through the study of some evidence of historical records, it was found that the beginning of cupping was known to world civilisations since the Sumerian kingdom was established around 4000 years BC, then developed and expanded towards Babylon, Egypt, Saba and the land drained by the Euphrates and Tigris Rivers